Google Sites as a Tool for Chemistry: Exploring the 8E Learning Cycle Approach - Pratiwi, Nani Arum; Zamhari, Muhammad; Ridzaniyanto, Pandu (Universitas Islam Indonesia, 2025)
The shift towards student-centered learning has heightened the demand for effective learning media in the digital era. Nevertheless, the availability of suitable resources remains limited. The fundamental laws of chemistry involve numerous complex concepts, making learning media essential to support student understanding. This study aims to develop and analyze Google Sites as a learning medium based on the 8E Learning Cycle to enhance the learning process of the fundamental laws of chemistry. The media was developed using the ADDIE model by Dick and Carey, limited to the development stage. Validation was conducted by one media expert and one material expert, while assessments were carried out by five high school chemistry teachers and 11 high school students. Google Sites as learning media developed interactively and compatible, combining the 8E Learning Cycle framework to improve student comperhension.. Validation results showed that media and material experts performed at 95.00% and 85.00%, respectively. The assessment of chemistry teachers was 94.33%, which is included in the very good category. In addition, student responses reached 100%. These findings indicate that the developed Google Sites learning media functions as an effective alternative that is in line with the principles of student-centered learning and supports students in understandingthe fundamental laws of chemistry.